Implementasi Closeness Centrality dalam Analisis Penyanyi Indonesia di DBpedia Indonesia - Nur Aini Rakhmawati; Ahmad Naufal Muzakki; Luthfi Lazuardi (JISKA (Jurnal Informatika Sunan Kalijaga), 2021)
Indonesian singers have a diverse musical genre. They also origin from several regions in Indonesia. This study analyzes the relationships between singers, genre, and origin of the singer using the Closeness Centrality algorithm. Data are retrieved by using a SPARQL query on DBpedia Indonesia. The generated graph produces a density value of 0.01. The results of the Closeness Centrality calculation shows that more than 50% out of 268 singers had scores above 30%.